Communication Analysis Of The Implementation Of The Implementation Of The Cash Direct Assistance (Blt) Program For The Impact Of Covid-19 - Zabibah, Isyah; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2022)
Direct Village Cash Assistance, hereinafter abbreviated as BLT Desa, is the provision of cash to poor or underprivileged families in the village to reduce the economic impact due to the Corona Virus Disease 2019 (COVID- 19) pandemic. 3 months. This study aims to analyze communication from the implementation of direct cash assistance. (BLT) in Lebo Village, analyze the obstacles to implementing the Covid-19 Cash Direct Assistance (BLT) policy in Lebo Sidoarjo Village. This research method is descriptive research using qualitative research, sampling technique using purposive sampling technique, data sources used in this study are primary and secondary data. Data analysis used descriptive qualitative analysis. The results of the study concluded that the indicators of Communication, Aspects of Transmission of the delivery of information directly through socialization. The aspect of clarity in the implementation of the Covid-19 BLT program in Lebo Village is the legal basis, among others, from the Instruction of the Minister of Home Affairs Number 3 of 2020, the Consistency Aspect is still not going well, in terms of the schedule for the distribution of the Covid 19 BLT in Lebo Village, it is not consistent with the existing regulations. Apply.